Development and characterization of curd fortified by pineapple juice - Dutta, Priyanka; Adhikari, Sunita; Chakraborty, Chaitali; Bandyopadhyay, Kakali; Paul, Anju; Ray, Subhajit (Indian Journal of Dairy Science, 2016)
Fruity curd is prepared by adding pineapple juice with lactic fermented milk. The physicochemical, organoleptic and rheological properties are analyzed to assay the quality of the curd. Physicochemical properties of curd samples including moisture, acidity, pH, ash, total carbohydrate and total polyphenols content are determined for all the samples. In this study, many trials have been done with different proportion of pineapple juice i.e. 5%, 7.5%, 10%, 12.5% and 15%. Initially due to bitterness of the final product, the process is modified by giving heat treatment to raw pineapple juice at 65 C for 10 min. Finally the sensory evaluation of the products are carried out and according to the panel of judges, overall acceptability of 12.5% juice fortified product is superior in comparison to others. Therefore, curd fortified with 12.5% pineapple juice is selected for further analysis i.e. moisture content, ash content, pH, acidity, total polyphenols content and total carbohydrates and the results are 69.11%, 1.23%, 5.08, 0.81%, 1.67g GAE/100g and 12.19g/100g respectively. The results of current study demonstrated that the addition of fruits to the curd significantly improved the quality of curd.